2019
DOI: 10.1093/nar/gkz782
|View full text |Cite
|
Sign up to set email alerts
|

Oxazinomycin arrests RNA polymerase at the polythymidine sequences

Abstract: Oxazinomycin is a C-nucleoside antibiotic that is produced by Streptomyces hygroscopicus and closely resembles uridine. Here, we show that the oxazinomycin triphosphate is a good substrate for bacterial and eukaryotic RNA polymerases (RNAPs) and that a single incorporated oxazinomycin is rapidly extended by the next nucleotide. However, the incorporation of several successive oxazinomycins or a single oxazinomycin in a certain sequence context arrested a fraction of the transcribing RNAP. The addition of Gre R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 101 publications
0
18
0
Order By: Relevance
“…For the DSI3 RNAP, the K m,app value for nucleotide incorporation on the CPD template was 560 6 110 mM (Fig. 7), significantly higher than previously reported K m values for undamaged templates (54,55). For the G1136M(DSI3) RNAP, this value was decreased to 120 6 15 mM (Fig.…”
Section: Mutations In the Tl Decrease K M For Nucleotide Substrates On Damaged Templatesmentioning
confidence: 62%
“…For the DSI3 RNAP, the K m,app value for nucleotide incorporation on the CPD template was 560 6 110 mM (Fig. 7), significantly higher than previously reported K m values for undamaged templates (54,55). For the G1136M(DSI3) RNAP, this value was decreased to 120 6 15 mM (Fig.…”
Section: Mutations In the Tl Decrease K M For Nucleotide Substrates On Damaged Templatesmentioning
confidence: 62%
“…S4B ; Methods M9 ). Their precise values are expected to vary for different nucleotides (9, 36, 37). We found that the values of k el and P total estimated by the fits are well captured by Eqs.…”
Section: Resultsmentioning
confidence: 99%
“…β'Q929M, Supplementary Fig. 2) could not be adequately fit by the previously employed reversible inactivation model 28,45,56 .…”
Section: Scenariomentioning
confidence: 91%
“…Overall, fits to Scheme 1 were performed largely as described in Prajapati et al 45 except that here we used a non-equilibrium heterogeneity model (see below) to describe the kinetic heterogeneity in the TEC preparations instead of a reversible inactivation model (see below)…”
Section: Supplementarymentioning
confidence: 99%